Role of website quality on online trust in e-commerce context - Dhaugoda, Sabina (2021)
Since the proliferation of electronic commerce (e-commerce) in the late nineties, an increasing number of customers are taking advantage of its benefits such as convenient online shopping, product/service search, price comparisons etc. However, lack of trust is one of the greatest barriers to online shopping and a major challenge that online businesses face. In today’s world, where competitors are just a click away, it is becoming more challenging for commercial websites to attract new customers and retain the existing ones. This study investigates the relationships between website quality, online trust, behavioural intentions and eWOM intentions in the e-commerce context. Five website quality dimensions were studied to find out which dimensions have a significant positive impact on the formation of online trust. Based on the research objectives, a research model was adopted from previous literature and developed. Seven hypotheses were proposed for the study. The research was conducted using a quantitative approach in which 310 responses were analysed using SPSS tool. The model was assessed using partial least squares structural equation modelling (PLS-SEM) in SmartPLS 3. The findings of this study support previous studies and hypotheses regarding significant influences of website aesthetics, website information quality, and security and privacy assurance on online trust. However, in contrast to the previous studies, website usability and speed of download didn’t have a significant influence on online trust. The results found that the most prominent website dimension is Website aesthetics because of its significant role in influencing online consumer trust by forming an initial impression of the site. Poor web interface causes rejection and mistrust of a website. Moreover, customers expect to find up-to-date information regarding products/services, company, as well as quality and easily accessible content. With the GDPR regulations in the EU, customers expect that online merchants ensure security and privacy concerns. Also, the result showed that positive online trust leads to an increase in behavioural and eWOM intentions. This study provides practical insights to managers about inducing online trust with a high-quality website.